PENTINGNYA PENGETAHUAN DIGITAL MARKETING UNTUK ENTREPREUNERSHIP - Mochamad Adhari Adiguna, M.Kom (JARI : Jurnal Pengabdian Kepada Masyarakat Republik Indonesia, 2023)
Developments in this era of globalization have created a digital era that is getting faster and faster. So, it requires various parties to be able to adapt to the new environment in this information technology, including business actors, both small, medium and large scale business actors. By using the internet network as a medium for doing business, businesses have a great opportunity to contribute to the global economic chain. By participating in using digital media in entrepreneurship, businesses can sell their products faster and can reduce operational costs / costs including very high distribution costs. The challenge that needs to be faced by business actors in this digital economy era is the low ability of human resources in dealing with trading methods from conventional to digital-based. One of these human resources is the participants of this activity, namely the students of Rumah Yatim and Pondok Pesantren Ruhama. In this community service activity (PKM), the expected output is that training participants can master and understand the importance of Digital Marketing Knowledge for entrepreneurship so that they have provisions or added value when they have to compete so that they can be accepted by the community when they leave Rumah Yatim and Pondok Pesantren Ruhama. This PKM will be held on March 18, 2023 at the Orphanage and Boarding School in Pengasinan District, Bogor Regency by involving Lecturers, Boarding School Staff and Pamulang University Students. The training participants are educators and education personnel as well as students at the Orphanage and Ruhama Islamic Boarding School to take part in this PKM activity. The Institute for Research and Community Service at Pamulang University (UNPAM), responds to concern for community problems by organizing Community Service activities in the form of "The Importance of Digital Marketing Knowledge for Entrepreunership. With our presence later, we hope that the participants from the Orphanage and Islamic Boarding School will open their insights about Digital Marketing applications, they can prepare earlier, so that when they enter the business world, they will be better prepared and have competitiveness with other entrepreneurs.